Safety and efficacy of a modified busulfan/cyclophosphamide conditioning regimen incorporating cladribine for autologous hematopoietic stem cell transplantation in acute myeloid leukemia - Shi, Yuan-Yuan; Liu, Zeng-Yan; Zhang, Gui-Xin; He, Yi; Han, Ming-Zhe; Feng, Si-Zhou; Zhang, Rong-Li; Jiang, Er-Lie (Frontiers in Pharmacology, 2023)
This is a small phase I study examining the safety and efficacy of a cladribine (CLAD)-containing conditioning regimen prior to autologous hematopoietic stem cell transplantion (auto-HSCT) for patients with acute myeloid leukemia (AML). All patients, aged 15-54 years (median 32 years), had favorable/intermediate risk AML (n = 20) or acute promyelocytic leu-kemia (APL; n = 2) and no evidence of minimal residual disease (MRD) prior to transplantation. Fourteen of the 22 patients received the conditioning regimen as follows: busulfan (Bu) + cyclophosphamide (Cy) + CLAD + cytarabine (Ara-c) or idarubicin. The conditioning regimen of 8 patients was without Cy nor ida-rubicin to reducing adverse cardiac reaction: the regimen of Bu + CLAD+ Ara-c for 6 patients; and the regimen of Bu + melphalan + CLAD + Ara-c for the other 2 patients. All 22 AML patients received peripheral blood stem cell transplantation. The number of infused mononuclear cells and CD34+ cells was 10.00 (2.88-20.97) × 108/kg and 1.89 (1.52-10.44) × 106/kg, re-spectively. Hematopoietic reconstitution was achieved in all patients, with a median time of 13 (10~34) days for neutrophils and 28 (14~113) days for platelets. Two patients suffered from pulmonary infection, 4 patients suf-fered from septicemia during the neutropenic stage, and the others suffered from infection or gastrointestinal reaction without exceeding grade 3 after conditioning, which were all alleviated by anti-infection and other support-ive treatment. None of the patients died of transplantation-related complica-tions. At a median follow-up of 29.5 (ranging from 4.0 to 60.0) months, three patients relapsed after auto-HSCT at a median time of 6 (ranging from 0.5 to 10.0) months. One patient died due to relapse at 18 months after au-to-HSCT. The remaining 21 patients were all alive, including 19 patients with negative MRD. The other 2 patients achieved negative MRD after al-logeneic HSCT or chemotherapy. The estimated 2-year survival, relapse, and Leukemia-free survival rates were 94.1±5.7%, 14.7±7.9% and 85.3±7.9%, respectively. A CLAD-combination conditioning regimen is efficient and safe for auto-HSCT, indicating an effective approach for AML treatment.